2001
DOI: 10.1086/318087
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles in Immunocompetent Persons Infected withMycobacterium aviumComplex

Abstract: To evaluate the immunologic factors that contribute to protection against Mycobacterium avium complex (MAC), cytokine production by peripheral blood mononuclear cells (PBMC) from human immunodeficiency virus-negative persons with pulmonary MAC (MAC patients) and healthy control subjects with a delayed hypersensitivity skin test response to M. avium sensitin (MAS-positive control subjects) was measured. In MAC patients, mycobacterium-stimulated PBMC produced higher concentrations of interleukin (IL)-10 but lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
81
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 49 publications
7
81
1
Order By: Relevance
“…Katalija et al showed that immune-modulating adipokines were abnormally regulated in patients with PNTM disease (23). Several studies reported decreased cytokine production and interferon-γ secretion in patients with PNTM disease (28)(29)(30). In our study, BMI was lower in patients with PNTM disease, in agreement with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Katalija et al showed that immune-modulating adipokines were abnormally regulated in patients with PNTM disease (23). Several studies reported decreased cytokine production and interferon-γ secretion in patients with PNTM disease (28)(29)(30). In our study, BMI was lower in patients with PNTM disease, in agreement with previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…The following Abs were used for immunolabeling: FITC anti-CD14, FITC anti-CD3, PE-conjugated anti-CD56, FITC anti-2B4, and PE-conjugated anti-DNAM-1 (all from BD Pharmingen), and immunostaining was performed by standard techniques (28). In some cases, indirect immunolabeling was performed using mouse mAb to human NKG2D (M585), MICA/B (6D4, as ascites), ULBP1, ULBP2, and ULBP3 (M295, M312, and M551, respectively; Amgen), and mouse polyclonal antisera specific for NKp46 and NKp30 as primary Abs (21) and a FITC goat anti-mouse secondary Ab (Southern Biotechnology Associates).…”
Section: Cytofluorometric Analysis and Absmentioning
confidence: 99%
“…To measure the percentages of PBMC that expressed CD3 and CD56, we used FITC-conjugated anti-CD3 and PE-conjugated anti-CD56 (both from BD PharMingen, San Diego, CA), and immunostaining was performed by standard techniques (7). Based on forward and side scatter characteristics, we gated on lymphocytes, and the percentages of single-and doublestained cells were determined with an EPICS flow cytometer (Coulter, Hialeah, FL).…”
Section: Cytofluorometric Analysismentioning
confidence: 99%